Pro Docker - Vohra, Deepak; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2016)
In this fast-paced book on the Docker open standards platform for developing, packaging and running portable distributed applications, Deepak Vorha discusses how to build, ship and run applications on any platform such as a PC, the cloud, data center or a virtual machine. He describes how to install and create Docker images. and the advantages off Docker containers.The remainder of the book is devoted to discussing using Docker with important software solutions. He begins by discussing using Docker with a traditional RDBMS using Oracle and MySQL. Next he moves on to NoSQL with chapter on MongoDB Cassandra, and Couchbase. Then he addresses the use of Docker in the Hadoop ecosystem with complete chapters on utilizing not only Hadoop, but Hive, HBase, Sqoop, Kafka, Solr and Spark. What You Will Learn How to install a Docker image How to create a Docker container How to run an Application in a Docker Container Use Docker with Apache Hadoop Ecosystem Use Docker with NoSQL Databases Use Docker with RDBMS Who This Book Is For Apache Hadoop Developers. Database developers. NoSQL Developers.
1. Hello Docker -- 2.Installing Linux -- 3.Oracle Database -- 4.MySQL Database -- 5.MongoDB -- 6.Apache Cassandra -- 7.Couchbase -- 8.Apache Hadoop -- 9.Apache Hive -- 10.Apache HBase -- 11.Apache Sqoop -- 12.Apache Kafka -- 13.Apache Solr -- 14.Apache Spark -- Appendix.
Keywords: Computer science; Software engineering; Database management; Computer Science; Database Management; Software Engineering; Electronic books